A robust reconfiguration protocol for the dynamic update of component‐based software systems. (26th April 2017) - Boyer, Fabienne; Gruber, Olivier; Pous, Damien
Summary: This paper focuses on the dynamic reconfiguration of component‐based software systems. From a structural point of view, such systems are made of components linked together through their provided and required services, the code of components being defined by modules (e.g., jar files). Today, the ability to reconfigure component‐based systems at runtime faces limitations. Some component frameworks allow to dynamically reconfigure components – starting or stopping them, or changing how they are wired together for instance – but forbid any dynamic evolution of the modules defining their code. Other frameworks allow to dynamically update modules but at the cost of loosing control on component wires, preventing software architects or tools alike to decide how components are wired together. In this paper, we propose a component framework that addresses these limitations through a unified approach for the management of components and modules. Our approach uniquely enables to reconfigure both components and modules at runtime, without restrictions. We prototyped the proposed framework in Java and exercised various dynamic reconfigurations of component‐based systems. Furthermore, we formalized this framework and proved the correctness of its reconfiguration protocol with the Coq proof assistant. Copyright © 2017 John Wiley & Sons, Ltd.